Proceedings of the 19th ACM Conference on Computer-Supported Cooperative Work &Amp; Social Computing 2016
DOI: 10.1145/2818048.2819928
|View full text |Cite
|
Sign up to set email alerts
|

Managing Expectations

Abstract: Extensive scholarship has investigated technology use among families. Existing work has focused primarily on parents' reactions to and restrictions of their children's technology use; here, we explore the underlying tensions surrounding technology use in the home. We draw on historical perspectives of adolescence and family life to better understand technology's impact on present-day parents and teens. Through an interview study with 18 parent-child pairs (19 parents; 23 children, ages 10-17), we find a number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(50 citation statements)
references
References 31 publications
2
46
0
2
Order By: Relevance
“…DISCUSSION Our findings reflect other studies regarding the variety of restrictions that parents place on their children's technology usage [5,8]. While not driven by security or privacy concerns, these do still serve to limit the exposure of children to digital threats.…”
Section: If I Need You Know To Go See Something I'm Gonna Know Hissupporting
confidence: 87%
See 1 more Smart Citation
“…DISCUSSION Our findings reflect other studies regarding the variety of restrictions that parents place on their children's technology usage [5,8]. While not driven by security or privacy concerns, these do still serve to limit the exposure of children to digital threats.…”
Section: If I Need You Know To Go See Something I'm Gonna Know Hissupporting
confidence: 87%
“…For example, previous studies examined family communication regarding technology use and online risks, and found that parents underestimate the important role of technology in their teens' lives [5,13]. Teens view digital spaces as completely personal and private spaces [6], and parents and teens agree on the right of teens to have some privacy [7].…”
mentioning
confidence: 99%
“…Despite these opportunities for text messaging to facilitate the development of autonomy from parents, there is also the potential for it to impair this developmental process if parents use texting as a way to drastically increase their oversight. In line with this, a few studies have found that the expectation of continuous contact is a source of conflict among adolescent–parent relationships (Blackwell, Gardiner, & Schoenebeck, ) and parents’ digital solicitations for information are less effective than in‐person soliciations (Hessel, He, & Dworkin, ). This suggests that although text messaging has the potential to promote autonomy, excessive parental contact via text might inhibit it.…”
Section: Developmental Tasks Of Adolescencementioning
confidence: 83%
“…There is work to suggest that parenting responsiveness and quality may suffer when attention is divided between phones and children. Anecdotally, parents believe they are better at focusing on their children when they intentionally put their phones away or do not use them during family time (Blackwell, Gardiner, & Schoenebeck, ; Radesky et al, ), and on average adults rate phone use as less appropriate when a child is present than when no child is present (Moser, Schoenebeck, & Reinecke, ). Experimental work also corroborates these anecdotes.…”
Section: How Does This Use Impact Parents and Parenting?mentioning
confidence: 99%